305 Reflections: Remade, Reworked, Reimagined: Sally Brown talks about place - Sally Brown; Ray Norman; Bill Boyd (Coolabah, 2013)
For quite a long time it has been claimed that cultural production in Tasmania has an inimitable and idiosyncratic place within the scheme of things. Sally Brown, a young Tasmanian designer, maker, artist, is unlikely to make this kind of claim for her work. Nonetheless, there is a particular sensibility evident in her work that it is doubtful that one might find anywhere other than in Tasmania – or made by someone of an older generation. This paper attempts to unpick, through four reflections upon Sally’s work, some of the thinking to do with the placedness, the vernacular social paradigm, the subliminal politics, the ‘crafting’ and the cultural savvy that gives Sally Brown’s work its presence. The questions that hang in the air around a collection of Sally Brown’s work are those to do with the ways local cultural imperatives might shape and make places they are found in, and in what ways might places shape the cultural realities that inhabit them. The following reflections on Sally’s work are distilled from email and blog conversations.